Curriculum Development for the Subject of â€œJadi Pendamping Adikâ€ in Class X - Sera, Marianus A.G; Situmorang, Robinson; Siregar, Eveline (Journal of Education Research and Evaluation, 2021)
The aim of this study was to develop curriculum of â€œJadi Pendamping Adikâ€ subject in class X of Sint Peter Catholic Senior High School in Ende. This study was research and development which used Dick and Carrey model as the procedur of curriculum development. The steps of the curriculum development were: identify instructional goal, conduct instructional analysis, analyze learnes and contexts, write specific learning objectives, develop assesment instrumen, develop instructional strategy, develop and select instructional materials, design and conduct formative evaluation of instruction, and revise. Data feasiblity analysis from the experts used qualitatif and quantitatif descriptive data analysis. The result of the feasibility analysis from the instructional design expert, the percentage of achievment level was 92.5% with a very good qualifications and feasible to be used with revisions as needed. The result of the feasibility analysis from each material experts was 90% and 92.5% with a very good qualifications and feasible to be used with revisions as needed. The curriculum development of â€œJadi Pendamping Adikâ€ subject in class X was feasible to be used as a guide in learning.